Resignification of the Pedagogical Leadership of School Leaders for the Transformation of Their Directive Practices - Chaucono Catrinao , Juan Carlos (2024)
The objective of this article is to redefine pedagogical practices to move towards leadership for learning in a school in the region of La Araucanía, Chile. The work subscribes to a case that uses a qualitative methodology. A total of 19 people participated, distributed among 17 teachers, 1 technical pedagogical head and 1 director. To collect the information, dialogic conversations between participants and reflections are carried out to deepen, from the perspective of the different actors, the understandings that they have built before, during and after the systematic questioning of the implicit representations about leadership rooted in thought and in its practice. The results indicate the predominance of pedagogical leadership practices focused on teacher teaching. Subsequently, to the improvement proposal co-constructed by teachers and directors, a gradual transition of the focus and approach of leadership in the school stands out, revealing small changes in the way of understanding learning. In conclusion, collaboratively establishing a professional learning route between teachers and managers from the implicit representations that you have built in your teaching career about what it means to teach, learn and evaluate, enables the implication to promote transformations in their practices from a leadership focused on teaching towards one focused on student learning.